The Role Of Primary Educational Planning in Implementing Education For Sustainale Development in Padang - Hami Mulyawan (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
This article aims to elaborate the role of Primary Educational planning in the level of District in implementing Education for Sustainable Development (ESD) in basic education in Padang District using the perspective of